Early Adolescent Alcohol Use: Are Sipping and Drinking Distinct? - Wadolowski, M.; Hutchinson, D.; Bruno, R.; Aiken, A.; Clare, P.; Slade, T.; Najman, J.; Kypri, K.; McBride, Nyanda; Mattick, R. (2015)
Background: Sipping alcohol is common during early adolescence, but research has ignored the distinction between sipping and drinking whole alcohol beverages, conflating the 2, or else simply classifying "sippers" as abstainers. Research has not addressed whether sippers are different to drinkers, in relation to variables known to be associated with adolescent alcohol consumption, or considered whether sipping and drinking behaviors may have quite different associations. Methods: Parent-child dyads (N = 1,823) were recruited in 3 states from Australian grade 7 classes. Multinomial logistic analyses compared adolescents who had only had a sip/taste of alcohol (sippers) with adolescents who had consumed at least a whole drink (drinkers) in the past 6 months. The multivariate model assessed a broad range of demographics, parenting practices, peer influences, and adolescent externalizing and internalizing behaviors, and controlled for school clustering. Results: Compared to drinkers, sippers were less likely to come from 1-parent households (odds ratio [OR] = 0.59, 95% confidence interval [CI]: 0.35 to 0.98); less likely to come from low-socioeconomic status (SES) households (OR = 0.54, 95% CI: 0.31 to 0.94); more likely to come from families where parents provide stricter alcohol-specific rules (OR = 1.21, 95% CI: 1.11 to 1.32), stricter monitoring of the child's activities (OR = 1.10, 95% CI: 1.04 to 1.16), more consistent parenting practices (OR = 1.13, 95% CI: 1.05 to 1.23), and more positive family relationships (OR = 1.56, 95% CI: 1.02 to 2.43); and report having fewer substance-using peers (OR = 0.80, 95% CI: 0.70 to 0.91) and greater peer disapproval of any substance use (OR = 1.30, 95% CI: 1.19 to 1.42). After adjustment for confounders, the associations with household composition and SES were no longer significant, but the familial and peer associations remained significant in the multivariate analysis, X2(40) = 1,493.06, p < 0.001. Conclusions: Sipping alcohol has different associations with known predictors of adolescent alcohol use than drinking whole beverages, and sipping may be a distinct or separable behavior. Future research should better define quantities of early consumption and assess the relationship between early sipping and drinking on long-term outcomes separately.